Healthcare access for children and families on the move and migrants. Issue 1 (13th April 2020) - Murphy, Lisa; Broad, Jonathan; Hopkinshaw, Bryony; Boutros, Sarah; Russell, Neal; Firth, Alison; McKeown, Rachael; Steele, Alison
Abstract : Background: The United Kingdom (UK) National Health Service (NHS) charging regulations have increasingly restricted migrants' healthcare access, in the context of a wider national policy shift over the past few years intending to create a 'hostile environment' for migrants. With an estimated 144 000 undocumented children living in the UK and increasing public concern that these regulations are negatively impacting migrant health and well-being, as well as contravening international child rights agreements, it has become imperative to understand their implications. Methods: A mixed methods digital survey, covering attitudes towards and understanding of UK healthcare charging, and giving space for relevant case submission, was disseminated through communications channels of the Royal College of Paediatrics and Child Health (RCPCH) to their members. Quantitative data were analysed on Stata, and basic proportions were calculated for each response proportion. Qualitative data were analysed using a framework analysis approach. Results: There were 200 responses, from a range of healthcare professional backgrounds. The majority were not confident in interpreting and applying the charging regulations. One-third (34%) reported examples of the charging regulations impacting patient care, analysis of which elicited seven key themes. Our survey gathered 18 cases of migrants being deterred from accessing healthcare, 11 cases of healthcare being delayed or denied outright, and 12 cases of delay in accessing care leading to worse health outcomes, including two intrauterine deaths. Discussion: Our results describe a range of harms arising from the current NHS charging regulations contributing to delays in or denials of healthcare, due to patients' fear of charging or immigration enforcement, including potential deportation, and confusion around entitlements. This harm affects individual patients, the migrant community and the NHS – often in multiple simultaneous ways. Many patients eligible for NHS care, such as trafficking victims, are not being identified as such. We found the current charging regulations to be unworkable, and that harm could not be eliminated simply through improved awareness or implementation.